Analisis Cara Pengenaan Biaya Disbursement Account dan Tingkat Pelayanan Kapal terhadap Daya Saing Perusahaan Keagenan Kapal di PT. Adhika Samudera Jaya - Hanny Amanda Rachmah; Faris Nofandi; Diyah Purwitasari (Globe: Publikasi Ilmu Teknik, Teknologi Kebumian, Ilmu Perkapalan, 2024)
The more rapid the development of the number of ship agency companies in Indonesia, the competition is also getting tighter. Therefore, ship agency companies must have a strategy to win the competition. One of the main factors to win the competition is the calculation of disbursement accounts and ship service levels. In the data taken, there is a relationship between the way disbursement account fees are charged and the level of ship service on the competitiveness of ship agency companies. Therefore, the author took the title "Analysis of How to Charge Disbursement Account Fees and Ship Service Levels on the Competitiveness of Ship Agency Companies". The purpose of writing this thesis is to determine the relationship between the method of charging disbursement account fees and the level of ship service on the competitiveness of ship agency companies. In this research, the author used quantitative methods. Correlation analysis is one of the steps to carry out an analysis of how shipping agency company account disbursement fees are charged and service quality on competitiveness. The results of the research concluded that the method of charging PT Disbursement Account Fees. Adhika Samudera Jaya is included in the very good category based on respondents' answers via questionnaire with an average of 4.70. PT. Service Level. Adhika Samudera Jaya is included in the very good category based on respondents' answers via questionnaire with an average of 4.68. There is a very strong, unidirectional and positive influence on the way disbursement account fees are charged and service levels on competitiveness at PT. Adhika Samudera Jaya with a correlation coefficient value of r = 0.813.